Pentingnya Asupan Gizi Seimbang untuk Meningkatkan Performa Atlet Muda: Perspektif dan Edukasi bagi Orang Tua Atlet di SSB Kancil Mas - Riska Anastasya Wijaya Kusuma; Linda Riski Sefrina; Milliyantri Elvandari (Universitas Muhamadiyah Manado, 2026)
Balanced nutrition intake is an important factor in supporting the performance of young athletes, especially during the growth period that requires optimal nutrition for intense physical activity. However, the lack of nutritional knowledge among parents of young athletes often leads to nutritional imbalances that have a negative impact on athlete health and performance. This study aims to measure the effect of balanced nutrition education on improving the knowledge and attitudes of parents of athletes at the Kancil Mas Football School (SSB), Karawang. The method used was a quasi-experiment with a pre-test and post-test design involving 20 respondents who were parents of U-13 athletes. Education was provided in the form of direct counseling sessions and group discussions, which were supplemented with supporting materials such as leaflets. The Wilcoxon signed rank test was used to analyze changes in parental knowledge and attitude scores before and after the intervention. The results of the analysis showed a significant increase in parents' understanding and positive attitudes towards balanced nutrition after education (p < 0.05). The results showed a significant increase in the level of parents' understanding and positive attitudes towards nutrition after the education intervention. These findings highlight the importance of active parental involvement in ensuring that young athletes' nutritional needs are met, as well as providing a basis for developing nutrition education programs in other sports schools.